FACTORS INFLUENCING THE IMPROVEMENT OF SOCIO-PEDAGOGICAL OPPORTUNITIES FOR DEVELOPING YOUTH POLITICAL CONSCIOUSNESS BASED ON NATIONAL VALUES - Nodirbek Murodov Oybek ugli (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Annotation: This article provides a comprehensive analysis of the system of factors influencing the improvement of socio-pedagogical opportunities for developing youth political consciousness based on national values. The study examines the interrelation and mechanisms of direct and indirect influence of socio-political, economic, cultural, pedagogical, psychological, and technological factors on the formation of youth political awareness. The article offers an in-depth analysis of state policy and the legal framework, the condition and potential of the education system, the role of the family environment and social institutions, the impact of globalization and digitalization processes, economic development and social stability, the national-cultural environment and value system, as well as demographic changes and youth characteristics. Within the context of Uzbekistan, the current state of these factors, their positive and negative effects, as well as strategic approaches and recommendations aimed at expanding socio-pedagogical opportunities and enhancing their effectiveness, are presented.